2010
DOI: 10.1111/j.1476-5381.2009.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Dog left ventricular midmyocardial myocytes for assessment of drug‐induced delayed repolarization: short‐term variability and proarrhythmic potential

Abstract: Background and purpose: Evaluation of the potential for delayed ventricular repolarization and proarrhythmia by new drugs is essential. We investigated if dog left ventricular midmyocardial myocytes (LVMMs) that can be used as a preclinical model to assess drug effects on action potential duration (APD) and whether in these cells, short-term variability (STV) or triangulation could predict proarrhythmic potential. Experimental approach: Beagle LVMMs and Purkinje fibres (PFs) were used to record APs. Effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 60 publications
2
44
0
Order By: Relevance
“…Studies involving the mechanisms underlying these cardiotoxicities revealed that TER blocks the human ether-a-go-go related gene (hERG), which is involved in expression of ion channels (e.g. K [37,38]. Defects in hERG lead to prolongation of the QT interval.…”
Section: Discussionmentioning
confidence: 99%
“…Studies involving the mechanisms underlying these cardiotoxicities revealed that TER blocks the human ether-a-go-go related gene (hERG), which is involved in expression of ion channels (e.g. K [37,38]. Defects in hERG lead to prolongation of the QT interval.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the fact that SV is considered one of the best proarrhythmic predictors [1,11,22] (but see also Michael et al 2007 [17]), its exact ionic mechanism is poorly understood. Involvement of many factors, such as stochastic gating of ion channels [14,18], cell-to-cell coupling [27], action potential duration and morphology [6], stimulation frequency [12] and intracellular calcium handling [13] in modulation of SV have been reported, however, neither their relative contribution, nor the role of the specific cardiac ion currents have been identified in a well defined experimental model.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in absence of relevant human cellular electrophysiological data, canine ventricular myocytes were chosen to analyze experimentally the determinants of SV in the present study due to two reasons. (1) Canine ventricular myocytes are believed to resemble human ventricular cells regarding their action potential morphology and kinetics of the underlying ion currents [19,20]; and (2) a large mass of in vitro and in vivo experimental data on beat-to-beat variability have been obtained in this species [1,12,13,15,22,23]. Here is to be mentioned that all action potentials analyzed in the present study were normally driven ones, records taken in myocytes displaying early or delayed afterdepolarizations were excluded from evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…In this hES-CMC system, we record the field potential duration (FPD)-as QT-like intervals-of clusters treated with a compound; we then calculate the corrected FPD (FPDc) and examine whether or not the compound prolongs FPDc. However, there have been reports that the QT interval is not a good surrogate marker of TdP and ventricular fibrillation [9][10][11][12][13][14][15][16][17][18]; the beat-to-beat variability of QT or QTc is suggested to be a better parameter [14,15]. It would therefore be of interest to investigate whether short-term variability in FPDc (STV FPDc ), as beat-to-beat variability, is increased along with FPDc prolongation in hES-CMCs treated with torsadogenic agents.…”
Section: Introductionmentioning
confidence: 99%